2007
DOI: 10.1189/jlb.0407206
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of angiostatic platelet factor-4 variant (CXCL4L1/PF-4var) versus inhibition of angiogenic granulocyte chemotactic protein-2 (CXCL6/GCP-2) in normal and tumoral mesenchymal cells

Abstract: Chemokines affect inflammation and cancer through leukocyte attraction and angiogenesis. Here, we demonstrate that CXCL4L1/platelet factor-4 variant (PF-4var), a highly angiostatic chemokine, is poorly chemotactic for phagocytes and is inducible in monocytes by inflammatory mediators but remained undetectable in macrophages and neutrophils. In addition, CXCL4L1/PF-4var production by mesenchymal tumor cells was evidenced in vitro and in vivo by specific ELISA and immunohistochemistry. CXCL4L1/PF-4var, but not C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…2D), indicating a stronger angiostatic activity of CXCL4L1/PF-4var 47-70 compared with CXCL4/PF-4 . For comparison, inhibition of endothelial cell migration was obtained at 20 nmol/L CXCL4/PF-4 or 1 nmol/L CXCL4L1/PF-4var, confirming previously published data (18,19). This allowed us to conclude that CXCL4L1/PF-4var is equally angiostatic as the intact chemokine.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…2D), indicating a stronger angiostatic activity of CXCL4L1/PF-4var 47-70 compared with CXCL4/PF-4 . For comparison, inhibition of endothelial cell migration was obtained at 20 nmol/L CXCL4/PF-4 or 1 nmol/L CXCL4L1/PF-4var, confirming previously published data (18,19). This allowed us to conclude that CXCL4L1/PF-4var is equally angiostatic as the intact chemokine.…”
Section: Discussionsupporting
confidence: 75%
“…As a control, CXCL4/PF-4 and CXCL4L1/PF-4var were also tested in this assay. The results confirm that CXCL4L1/PF-4var inhibits endothelial cell migration at 1 nmol/L, being therefore a 20-fold more potent inhibitor than CXCL4/PF-4 (18,19). Next, it was found that both PF-4 peptides (from 5 nmol/L onwards) significantly inhibited FGF-2-induced HUVEC motility as observed by time-lapse microscopy ( Fig.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations